Nonlinear Dynamics of a Nutrient-Phytoplankton Model with Time Delay - DeBing Mei; Min Zhao; Hengguo Yu; Chuanjun Dai; Yi Wang (Discrete Dynamics in Nature and Society)
We consider a nutrient-phytoplankton model with a Holling type II functional response and a time delay. By selecting the time delay used as a bifurcation parameter, we prove that the system is stable if the delay value is lower than the critical value but unstable when it is above this value. First, we investigate the existence and stability of the equilibria, as well as the existence of Hopf bifurcations. Second, we consider the direction, stability, and period of the periodic solutions from the steady state based on the normal form and the center manifold theory, thereby deriving explicit formulas. Finally, some numerical simulations are given to illustrate the main theoretical results.